The possible mitigating effect of hawthorn on some cold stress-induced changes in rats - Samah El-Metwally Ibrahim; Hanan F Al-Saeed; Yousuf A. F. (Wolters Kluwer Medknow Publications, 2021)
Background Cold stress is one of the potentially life-threatening challenges that could exert dramatic effects on adult health. Cold stress could affect the synthesis of some important neuroproteins and increase the susceptibility for infection. Besides, it is one of the famous predisposing causes that can affect mood and result in actual mood effect. Hawthorn plant possesses various bioactive natural compounds. However, there has been little attempt toward exploring the potential health effects of hawthorn. Objective The aim of the research is to validate if hawthorn extract could be used as a strategy against the multiple health adverse effects that might result from cold stress. Materials and methods A total of 50 adult male albino rats were equally divided into five groups: control; hawthorn administered; cold stress exposed; cold stress exposed and pretreated by hawthorn; and cold stress-exposed and concomitantly treated by hawthorn. Blood samples were collected to investigate the proinflammatory markers, such as serum interleukin-6 (IL-6), oxidative stress markers, superoxide dismutase (SOD), and malondialdehyde (MDA), as well as the brain-derived neurotrophic factor (BDNF). Results Rats exposed to cold stress showed significant increase in serum IL-6 and MDA, whereas serum SOD and BDNF were significantly decreased. Fortunately, hawthorn-administered rats revealed alleviation of these disturbances, as serum IL-6 and MDA were significantly decreased, with an associated significant increases in serum SOD as well as BDNF. Conclusion Hawthorn extract can be used as a neuromodulator, an antioxidant, and an anti-inflammatory agent for reversing the adverse effects of cold stress.